Pharmacogenomics Statins: Biomarkers for Clinical Prediction - Suprapti, Herni (Universitas Wijaya Kusuma Surabaya, 2018)
Statins are the most widely prescribed drug for hyperlipidemic therapy and for the prevention of Cardiovascular disease. But although statins are very effective for the prevention of atherosclerosis, there are still patients with CVD. In this case, it is thought to be the influence of genetic factors. There is a static gene link to statin dose required for therapy, but there are still no relevant pharmacogenomic tests for statin therapy guidelines. This article describes basic pharmacogenomic terminology, genes (CETP, HMGCR, SLCO1B1, ABCB1, and CYP3A4 / 5), and progression of statin pharmacogenomic biomarkers for predicted therapeutic outcomes.